Peranan Bahasa Arab Terhadap Ilmu Pengetahuan - Latifah Salim (Jurnal Adabiyah: Humanities and Islamic Studies, 2015)
Arabic language has significant roles in developing science. In the time of Umayyah and Abbasiyah Dynasty, Arabic had been used as means to translate some scientific books of Greek Philosophy. It resulted in the change of Moslem thought. The huge translation motivated some experts to develop their skill and knowledge. Through this language, people can understand the development of science. Not only could the people of Middle East enjoy the depelopment of science but western people as well.